Lyle, Lyle, crocodile - Waber, Bernard (Boston : Houghton Mifflin, 1993)
Lyle is perfectly happy living with the Primms on East 88th St. until irritable Mr. Grumps next door changes all that.
Elem. School Library Collection.
School Library Journal.
Wilson's Children.
Booklist, June 2010.
Bulletin (Center for Children's books), October 2009.
Elem. School Library Collection, June 2000.
Keywords: Crocodiles -- Juvenile fiction; Crocodiles -- Fiction; Crocodiles -- Fiction; Picture books for children